Symptom Burden and Unmet Existential Needs in Adults With Cystic Fibrosis. (October 2019) - Trandel, Elizabeth T.; Pilewski, Joseph M.; Dellon, Elisabeth P.; Moreines, Laura T.; Yabes, Jonathan G.; Jeong, Kwonho; Arnold, Robert M.; Kavalieratos, Dio
Although patients with cystic fibrosis (CF) experience many symptoms and impaired quality of life, little is known about existential distress. This multivariable logistic regression evaluated the relationship between symptom burden and five existential needs representing existential distress in 164 adults with CF. Eleven percent of participants reported no symptom burden, 61% mild burden, and 28% moderate/severe burden. The most prevalent existential needs were fears about CF worsening (50%) and uncertainty about the future (39%). Participants with moderate/severe symptom burden were likelier to report needing support with all five needs than participants with no or mild burden. For each six-point increase in burden, there was an increased odds of reporting need for support with learning to feel in control, feelings about death and dying, fears about CF worsening, uncertainty about the future, and concerns about worries of others. CF-specific palliative care support based on these prevalent unmet existential needs should be developed and provided.